Recycled aggregate environment-friendly anti-crack premixed concrete and preparation method thereof
Through the preparation of modified regenerated aggregate powder, chemical treatment methods such as exciters and aminosilanes are used to generate organic cladding materials, which solves the problem of insufficient performance of regenerated aggregate concrete in terms of strength, permeability, crack resistance and shrinkage resistance, and achieves better performance.
Patent Information
- Application Number
- CN202510140917.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-15
AI Technical Summary
The existing recycled aggregate concrete has insufficient performance in terms of strength, permeability, crack resistance and shrinkage resistance. It is mainly due to the tiny cracks and pores of the recycled aggregate, resulting in poor interface bonding, insufficient hydration reaction, and easy cracking.
Modified regenerated aggregate powder is used to generate organic cladding materials through exciter soaking, aminosilane treatment and click chemical reactions, which fill the cracks and gaps of the aggregate, and enhance the interface combination with the concrete matrix.
The strength, seepage resistance, crack resistance and shrinkage resistance of recycled aggregate concrete have been significantly improved, and the problem of insufficient performance of recycled aggregate concrete in these aspects has been solved.
Smart Images

Figure BDA0005264830030000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, and in particular to a recycled aggregate environmentally friendly crack-resistant ready-mixed concrete and a preparation method thereof. Background Art
[0002] As the demand for concrete increases, it is inevitable to mine a large amount of sand and gravel and consume various resources, resulting in the exploitation and destruction of natural resources. Secondly, with the construction of new roads and the reconstruction of old roads, a large amount of waste concrete is generated. The recycling and reuse of waste concrete is an effective measure to solve the above problems. Recycled aggregate concrete utilizes the characteristics of recycled aggregates, realizes the recycling of waste concrete, brings significant economic and environmental benefits, and has far-reaching significance for social development.
[0003] From the perspective of the preparation of recycled aggregates, during the crushing process, the internal part of the aggregates will be more or less damaged, and the resulting aggregates will have many tiny cracks. In addition, the crushing index is generally high, resulting in a higher powder content than natural sand. At the same time, more cracks and pores lead to a higher water absorption rate. After entering the concrete, it will strongly absorb the moisture in the cement material at its interface, resulting in insufficient hydration of the cement material and failure to generate sufficient hydration products, resulting in poor interface bonding between the recycled aggregate and the concrete matrix, and the concrete is prone to cracking when subjected to load. Therefore, the performance indicators of concrete prepared by directly using the recycled aggregate formed by crushing waste concrete to replace natural aggregates are insufficient in strength, impermeability, crack resistance and other performance indicators. Summary of the invention
[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a recycled aggregate environmentally friendly crack-resistant ready-mixed concrete and a preparation method thereof.
[0005] The purpose of the present invention is achieved by the following technical solutions:
[0006] In a first aspect, the present invention provides a recycled aggregate environmentally friendly crack-resistant ready-mixed concrete, which comprises the following components calculated by weight:
[0007] 70-120 parts of Portland cement, 115-178 parts of coarse aggregate, 182-269 parts of fine aggregate, 96-152 parts of modified recycled aggregate powder, 18-24 parts of fly ash, 1.3-2.6 parts of water reducer and 80-100 parts of water.
[0008] Preferably, the silicate cement is ordinary silicate cement P.O42.5.
[0009] Preferably, the coarse aggregate is stone with a particle size between 4.75-10 mm; and the fine aggregate is fine sand with a particle size less than 4.75 mm.
[0010] Preferably, the fly ash is secondary fly ash with a particle size of 16-25 μm, a loss on ignition of no more than 8%, a water content of no more than 1%, and a sulfur trioxide content of no more than 3%.
[0011] Preferably, the water reducer is one of polycarboxylic acid high-efficiency water reducer CC-AI, polycarboxylic acid high-efficiency water reducer CC-AII and polycarboxylic acid high-efficiency water reducer CC-B.
[0012] Preferably, the method for preparing the modified recycled aggregate powder comprises:
[0013] S1, washing and drying the waste concrete aggregate, and then crushing it in a crusher to obtain waste aggregate powder;
[0014] S2. Weigh sodium hydroxide powder and deionized water, mix them in a container, stir them thoroughly at room temperature until they are completely dissolved, then slowly pour them into a water glass, stir them thoroughly, and then seal the container and let it stand for 10-16 hours to obtain an activator;
[0015] S3, then soaking the waste aggregate powder in the activator, stirring continuously for 1-2 hours, filtering and collecting solid particles, and then heating, washing and drying to obtain the preliminary treated waste aggregate powder;
[0016] S4. Weigh dimethyldimethylaminovinylsilane and add it to anhydrous ethanol, then add the preliminary treated material of waste aggregate powder, soak for 2-4 hours, then add 2-mercaptobenzimidazole, after fully dispersing, irradiate with ultraviolet light and stir for 1-3 hours under the action of initiator, after the treatment is completed, filter and collect the powder, and after drying, the modified recycled aggregate powder is obtained.
[0017] Preferably, in S1, the waste concrete aggregate is washed with water for 2-5 times, and the drying is performed by sun drying or oven drying.
[0018] Preferably, in S1, the crushed concrete aggregate is sieved through a 50-150 mesh sieve.
[0019] Preferably, in S2, the modulus of water glass is 1.2-2.8, and the mass ratio of sodium hydroxide powder, deionized water and water glass is 1-3:4-6:10-20.
[0020] Preferably, in S3, the mass ratio of the waste aggregate powder to the activator is 1:2-5.
[0021] Preferably, in S3, the temperature of the heating treatment is 50-60°C, the time of the heat preservation treatment is 5-10h; the washing is performed by washing with clean water for 3-5 times; and the drying is performed at 110-120°C for 1-2h.
[0022] Preferably, in S4, the mass ratio of the preliminary treated waste aggregate powder, dimethyldimethylaminovinylsilane, 2-mercaptobenzimidazole and anhydrous ethanol is 1:0.1-0.2:0.07-0.15:10-20.
[0023] Preferably, in S4, the initiator is photoinitiator 1173 or photoinitiator 907.
[0024] Preferably, in S4, the wavelength of the ultraviolet light is 365nm and the light intensity is 10-20mw / cm 2 .
[0025] In a second aspect, the present invention provides a method for preparing environmentally friendly crack-resistant ready-mixed concrete made of recycled aggregate, comprising the following steps:
[0026] Step 1, first mix silicate cement, coarse aggregate, fine aggregate, fly ash and modified recycled aggregate powder into a mortar mixer, and stir at a speed of 50-100 r / min for 2-6 minutes to obtain a first mixture;
[0027] Step 2, adding a water reducer to water, stirring evenly, and then pouring it into the first mixture, stirring at a speed of 50-100 r / min for 4-10 min to obtain a concrete mixture;
[0028] Step 3, after the concrete mixture is transported to the use site, it is poured and constructed, and after being vibrated and degassed, it is watered and cured for 7-28 days after being formed, and the environmentally friendly and crack-resistant ready-mixed concrete is obtained.
[0029] The beneficial effects of the present invention are:
[0030] 1. The present invention prepares a new type of recycled aggregate ready-mixed concrete. Compared with conventional recycled aggregate, the present invention performs modification on the recycled aggregate. The concrete material prepared using the modified recycled aggregate powder has excellent performance in strength, impermeability, crack resistance and shrinkage resistance.
[0031] 2. The modification process of recycled aggregates of the present invention includes: firstly, the discarded concrete aggregates after crushing are soaked with an activator to promote the hydration reaction of the aluminosilicate components in the discarded aggregates, so that the tiny cracks in the aggregates are filled and reinforced; then, the hydrated discarded aggregates are soaked in a solution containing aminosilanes with unsaturated double bonds, so that the aminosilanes with unsaturated bonds can be dispersed and adsorbed in the aggregates; and then 2-mercaptobenzimidazole is added to generate a compound coating material in the gaps or on the surface of the aggregates by utilizing the click chemistry reaction of the double bond-mercapto group, thereby completing the modification of the recycled aggregates.
[0032] 3. The surface and gaps of the modified recycled aggregate prepared by the present invention are filled with an organic coating material containing a large amount of amino, silane, sulfide and benzimidazole groups. The organic coating material not only has a better filling property for cracks in the recycled aggregate, but also enhances the interface bonding with the concrete matrix. At the same time, it can also make up for the defect that the recycled aggregate is prone to cracking during hydration reaction. Ultimately, it has a good enhancing effect on the strength, impermeability, crack resistance, and especially shrinkage resistance of the recycled concrete. DETAILED DESCRIPTION
[0033] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0034] The present invention will be further described below in conjunction with the following examples.
[0035] Example 1
[0036] A recycled aggregate environmentally friendly crack-resistant ready-mixed concrete, calculated by weight, includes the following components:
[0037] 95 parts of Portland cement, 154 parts of coarse aggregate, 227 parts of fine aggregate, 123 parts of modified recycled aggregate powder, 21 parts of fly ash, 1.8 parts of water reducer and 90 parts of water.
[0038] Among them, the silicate cement is ordinary silicate cement P.O42.5; the coarse aggregate is stone with a particle size between 4.75-10mm; the fine aggregate is fine sand with a particle size less than 4.75mm; the fly ash is secondary fly ash with a particle size of 16-25μm, a loss on ignition of not more than 8%, a water content of not more than 1%, and a sulfur trioxide content of not more than 3%; the water reducer is polycarboxylic acid high-efficiency water reducer CC-AI.
[0039] The preparation method of modified recycled aggregate powder comprises:
[0040] S1, take the discarded concrete aggregate (apparent density 2246kg / m 3 , average compressive strength is 32.6MPa, SiO2 content is 52.3%, CaO content is 27.4%); the waste concrete aggregate is washed with water for 3 times and then air-dried, and then crushed in a crusher, passed through a 100-mesh sieve, and waste aggregate powder is obtained;
[0041] S2, weigh sodium hydroxide powder and deionized water and mix them in a container, stir them thoroughly at room temperature until they are completely dissolved, then slowly pour them into water glass with a modulus of 2.2, the mass ratio of sodium hydroxide powder, deionized water and water glass is 2:5:15, stir them thoroughly, then seal the container, and let it stand for 12 hours to obtain an activator;
[0042] S3, then soaking the waste aggregate powder in the activator, the mass ratio of the waste aggregate powder to the activator is 1:3, stirring continuously for 1.5 hours, filtering and collecting solid particles, and then placing the solid particles in an oven at 50-60°C for 8 hours, and then washing with clean water for 4 times, and drying at 110°C for 2 hours to obtain the preliminary treated waste aggregate powder;
[0043] S4. Weigh dimethyldimethylaminovinylsilane and add it to anhydrous ethanol, then add the preliminary treatment of waste aggregate powder, soak for 3 hours, and then add 2-mercaptobenzimidazole. The mass ratio of the preliminary treatment of waste aggregate powder, dimethyldimethylaminovinylsilane, 2-mercaptobenzimidazole and anhydrous ethanol is 1:0.15:0.11:15. After being fully dispersed, under the action of photoinitiator 1173 (the addition amount is 3% of 2-mercaptobenzimidazole), the wavelength is 365nm and the light intensity is 15mw / cm 2 The mixture was irradiated with ultraviolet light and stirred for 2 hours. After the treatment, the powder was collected by filtration and dried to obtain the modified recycled aggregate powder.
[0044] The method for preparing the above-mentioned recycled aggregate environmentally friendly crack-resistant ready-mixed concrete comprises the following steps:
[0045] Step 1, first mix silicate cement, coarse aggregate, fine aggregate, fly ash and modified recycled aggregate powder into a mortar mixer, and stir at a speed of 80 r / min for 4 minutes to obtain a first mixture;
[0046] Step 2, adding a water reducing agent to water, stirring evenly, and then pouring it into the first mixture, stirring at a speed of 100 r / min for 8 minutes to obtain a concrete mixture;
[0047] Step 3, after the concrete mixture is transported to the use site, it is poured and constructed, and after being vibrated and degassed, it is watered and cured for 28 days after being formed, and the environmentally friendly and crack-resistant ready-mixed concrete is obtained.
[0048] Example 2
[0049] A recycled aggregate environmentally friendly crack-resistant ready-mixed concrete, calculated by weight, includes the following components:
[0050] 70 parts of Portland cement, 115 parts of coarse aggregate, 182 parts of fine aggregate, 96 parts of modified recycled aggregate powder, 18 parts of fly ash, 1.3 parts of water reducer and 80 parts of water.
[0051] Among them, the silicate cement is ordinary silicate cement P.O42.5; the coarse aggregate is a stone with a particle size between 4.75-10mm; the fine aggregate is fine sand with a particle size less than 4.75mm; the fly ash is secondary fly ash with a particle size of 16-25μm, a loss on ignition of not more than 8%, a water content of not more than 1%, and a sulfur trioxide content of not more than 3%; the water reducer is a polycarboxylic acid high-efficiency water reducer CC-AII; the preparation method of the modified recycled aggregate powder is the same as that in Example 1.
[0052] The method for preparing the above-mentioned recycled aggregate environmentally friendly crack-resistant ready-mixed concrete comprises the following steps:
[0053] Step 1, firstly mix silicate cement, coarse aggregate, fine aggregate, fly ash and modified recycled aggregate powder into a mortar mixer, and stir at a speed of 50 r / min for 6 min to obtain a first mixture;
[0054] Step 2, adding a water reducing agent to water, stirring evenly, and then pouring it into the first mixture, stirring at a speed of 50 r / min for 10 minutes to obtain a concrete mixture;
[0055] Step 3, after the concrete mixture is transported to the use site, it is poured and constructed, and after being vibrated and degassed, it is watered and cured for 28 days after being formed, and the environmentally friendly and crack-resistant ready-mixed concrete is obtained.
[0056] Example 3
[0057] A recycled aggregate environmentally friendly crack-resistant ready-mixed concrete, calculated by weight, includes the following components:
[0058] 120 parts of Portland cement, 178 parts of coarse aggregate, 269 parts of fine aggregate, 152 parts of modified recycled aggregate powder, 24 parts of fly ash, 2.6 parts of water reducer and 100 parts of water.
[0059] Among them, the silicate cement is ordinary silicate cement P.O42.5; the coarse aggregate is a stone with a particle size between 4.75-10mm; the fine aggregate is fine sand with a particle size less than 4.75mm; the fly ash is secondary fly ash with a particle size of 16-25μm, a loss on ignition of not more than 8%, a water content of not more than 1%, and a sulfur trioxide content of not more than 3%; the water reducer is a polycarboxylic acid high-efficiency water reducer CC-B; the preparation method of the modified recycled aggregate powder is the same as that in Example 1.
[0060] The method for preparing the above-mentioned recycled aggregate environmentally friendly crack-resistant ready-mixed concrete comprises the following steps:
[0061] Step 1, first mix silicate cement, coarse aggregate, fine aggregate, fly ash and modified recycled aggregate powder into a mortar mixer, and stir at a speed of 100 r / min for 2 minutes to obtain a first mixture;
[0062] Step 2, adding a water reducing agent to water, stirring evenly, and then pouring it into the first mixture, stirring at a speed of 100 r / min for 4 minutes to obtain a concrete mixture;
[0063] Step 3, after the concrete mixture is transported to the use site, it is poured and constructed, and after being vibrated and degassed, it is watered and cured for 28 days after being formed, and the environmentally friendly and crack-resistant ready-mixed concrete is obtained.
[0064] Example 4
[0065] A recycled aggregate environmentally friendly crack-resistant ready-mixed concrete, which differs from Example 1 only in that the preparation method of the modified recycled aggregate powder is different.
[0066] The preparation method of modified recycled aggregate powder comprises:
[0067] S1, take waste concrete aggregate; rinse the waste concrete aggregate with water twice and then dry it in the sun, then crush it in a crusher, pass it through a 50-mesh sieve, and obtain waste aggregate powder;
[0068] S2, weigh sodium hydroxide powder and deionized water, mix them in a container, stir them thoroughly at room temperature until they are completely dissolved, and then slowly pour them into water glass with a modulus of 1.2, the mass ratio of sodium hydroxide powder, deionized water and water glass is 1:4:10, stir them thoroughly, and then seal the container and let it stand for 10 hours to obtain an activator;
[0069] S3, then soaking the waste aggregate powder in the activator, the mass ratio of the waste aggregate powder to the activator is 1:2, stirring continuously for 1 hour, filtering and collecting solid particles, and then placing the solid particles in an oven at 50° C. for 5 hours, and then washing with clean water for 3 times, and drying at 110° C. for 1 hour to obtain the preliminary treated waste aggregate powder;
[0070] S4. Weigh dimethyldimethylaminovinylsilane and add it to anhydrous ethanol, then add the preliminary treatment of waste aggregate powder, soak for 2 hours, and then add 2-mercaptobenzimidazole. The mass ratio of the preliminary treatment of waste aggregate powder, dimethyldimethylaminovinylsilane, 2-mercaptobenzimidazole and anhydrous ethanol is 1:0.1:0.07:10. After being fully dispersed, under the action of photoinitiator 1173 (the addition amount is 8% of 2-mercaptobenzimidazole), use a wavelength of 365nm and a light intensity of 10mw / cm 2 The mixture was irradiated with ultraviolet light and stirred for 1 hour. After the treatment, the powder was collected by filtration and dried to obtain the modified recycled aggregate powder.
[0071] Example 5
[0072] A recycled aggregate environmentally friendly crack-resistant ready-mixed concrete, which differs from Example 1 only in that the preparation method of the modified recycled aggregate powder is different.
[0073] The preparation method of modified recycled aggregate powder comprises:
[0074] S1, take waste concrete aggregate; rinse the waste concrete aggregate with water 5 times and then dry it in the sun, then crush it in a crusher, pass it through a 150-mesh sieve, and obtain waste aggregate powder;
[0075] S2, weigh sodium hydroxide powder and deionized water and mix them in a container, stir them thoroughly at room temperature until they are completely dissolved, then slowly pour them into water glass with a modulus of 2.8, the mass ratio of sodium hydroxide powder, deionized water and water glass is 3:6:20, stir them thoroughly, then seal the container, and let it stand for 16 hours to obtain an activator;
[0076] S3, then soaking the waste aggregate powder in the activator, the mass ratio of the waste aggregate powder to the activator is 1:5, and after continuous stirring for 2 hours, filtering and collecting solid particles, and then placing the solid particles in an oven at 60° C. for 10 hours, and then washing with clean water for 5 times, and drying at 120° C. for 2 hours to obtain the preliminary treated waste aggregate powder;
[0077] S4. Weigh dimethyldimethylaminovinylsilane and add it to anhydrous ethanol, then add the preliminary treatment of waste aggregate powder, soak for 4 hours, and then add 2-mercaptobenzimidazole. The mass ratio of the preliminary treatment of waste aggregate powder, dimethyldimethylaminovinylsilane, 2-mercaptobenzimidazole and anhydrous ethanol is 1:0.2:0.15:20. After being fully dispersed, under the action of photoinitiator 907 (the addition amount is 2% of 2-mercaptobenzimidazole), use a wavelength of 365nm and a light intensity of 20mw / cm 2 The mixture was irradiated with ultraviolet light and stirred for 3 hours. After the treatment, the powder was collected by filtration and dried to obtain the modified recycled aggregate powder.
[0078] Comparative Example 1
[0079] A recycled aggregate ready-mixed concrete, which is different from Example 1 only in that the preparation method of the modified recycled aggregate powder is different. In this comparative example, only the waste aggregate powder is treated with an activator to prepare the modified recycled aggregate powder.
[0080] The preparation method of modified recycled aggregate powder comprises:
[0081] S1, take the discarded concrete aggregate (apparent density 2246kg / m 3, the average compressive strength is 32.6MPa); the waste concrete aggregate is washed with water three times and then dried in the sun, and then crushed in a crusher, passed through a 100-mesh sieve, and the waste aggregate powder is obtained;
[0082] S2, weigh sodium hydroxide powder and deionized water and mix them in a container, stir them thoroughly at room temperature until they are completely dissolved, then slowly pour them into water glass with a modulus of 2.2, the mass ratio of sodium hydroxide powder, deionized water and water glass is 2:5:15, stir them thoroughly, then seal the container, and let it stand for 12 hours to obtain an activator;
[0083] S3. Then soak the waste aggregate powder in the activator. The mass ratio of the waste aggregate powder to the activator is 1:3. After continuous stirring for 1.5 hours, filter and collect the solid particles. Then place the solid particles in an oven at 50-60°C for 8 hours, wash them with clean water for 4 times, and dry them at 110°C for 2 hours to obtain the modified recycled aggregate powder.
[0084] Comparative Example 2
[0085] A recycled aggregate ready-mixed concrete, which differs from Example 1 only in that the preparation method of the modified recycled aggregate powder is different. In this comparative example, the waste aggregate powder is treated with an activator and then treated with dimethyldimethylaminovinylsilane to prepare the modified recycled aggregate powder.
[0086] The preparation method of modified recycled aggregate powder comprises:
[0087] S1, take the discarded concrete aggregate (apparent density 2246kg / m 3 , the average compressive strength is 32.6MPa); the waste concrete aggregate is washed with water three times and then dried in the sun, and then crushed in a crusher, passed through a 100-mesh sieve, and the waste aggregate powder is obtained;
[0088] S2, weigh sodium hydroxide powder and deionized water and mix them in a container, stir them thoroughly at room temperature until they are completely dissolved, then slowly pour them into water glass with a modulus of 2.2, the mass ratio of sodium hydroxide powder, deionized water and water glass is 2:5:15, stir them thoroughly, then seal the container, and let it stand for 12 hours to obtain an activator;
[0089] S3, then soaking the waste aggregate powder in the activator, the mass ratio of the waste aggregate powder to the activator is 1:3, stirring continuously for 1.5 hours, filtering and collecting solid particles, and then placing the solid particles in an oven at 50-60°C for 8 hours, and then washing with clean water for 4 times, and drying at 110°C for 2 hours to obtain the preliminary treated waste aggregate powder;
[0090] S4. Weigh dimethyldimethylaminovinylsilane and add it to anhydrous ethanol, then add the preliminary treated material of waste aggregate powder. The mass ratio of the preliminary treated material of waste aggregate powder, dimethyldimethylaminovinylsilane and anhydrous ethanol is 1:0.26:15. After soaking for 2-4 hours, filter and collect the powder. After drying, the modified recycled aggregate powder is obtained.
[0091] Comparative Example 3
[0092] A recycled aggregate ready-mixed concrete, which differs from Example 1 only in that the preparation method of the modified recycled aggregate powder is different. In this comparative example, the waste aggregate powder is treated with an activator and then treated with dimethyldimethylaminovinylsilane to prepare the modified recycled aggregate powder.
[0093] The preparation method of modified recycled aggregate powder comprises:
[0094] S1, take the discarded concrete aggregate (apparent density 2246kg / m 3 , the average compressive strength is 32.6MPa); the waste concrete aggregate is washed with water three times and then dried in the sun, and then crushed in a crusher, passed through a 100-mesh sieve, and the waste aggregate powder is obtained;
[0095] S2, weigh sodium hydroxide powder and deionized water and mix them in a container, stir them thoroughly at room temperature until they are completely dissolved, then slowly pour them into water glass with a modulus of 2.2, the mass ratio of sodium hydroxide powder, deionized water and water glass is 2:5:15, stir them thoroughly, then seal the container, and let it stand for 12 hours to obtain an activator;
[0096] S3, then soaking the waste aggregate powder in the activator, the mass ratio of the waste aggregate powder to the activator is 1:3, stirring continuously for 1.5 hours, filtering and collecting solid particles, and then placing the solid particles in an oven at 50-60°C for 8 hours, and then washing with clean water for 4 times, and drying at 110°C for 2 hours to obtain the preliminary treated waste aggregate powder;
[0097] S4. Weigh 2-mercaptobenzimidazole and add it to anhydrous ethanol, then add the preliminary treated material of waste aggregate powder, the mass ratio of the preliminary treated material of waste aggregate powder, 2-mercaptobenzimidazole and anhydrous ethanol is 1:0.26:15. After soaking for 2-4 hours, filter and collect the powder, and after drying, obtain the modified recycled aggregate powder.
[0098] Experimental testing
[0099] The properties of the recycled aggregate ready-mixed concrete prepared in Example 1 and Comparative Examples 1-3 were tested and compared. The compressive strength was referenced to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the crack resistance was referenced to JGJ / T 193-2009 "Standard for Testing and Evaluation of Durability of Concrete", the impermeability was referenced to GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", and the shrinkage was referenced to GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The test results are shown in Table 1:
[0100] Table 1 Performance of different ready-mixed concrete
[0101]
[0102] It can be seen from the test results in Table 1 that the recycled aggregate ready-mixed concrete prepared in Example 1 of the present invention has better compressive strength than that of Comparative Examples 1-3 both at 7 days and 28 days, and also has excellent crack resistance and impermeability, and is more excellent in shrinkage resistance.
[0103] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0104] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A recycled aggregate environmentally friendly crack-resistant ready-mixed concrete, characterized in that: Calculated by weight, it includes the following ingredients: 70-120 parts of Portland cement, 115-178 parts of coarse aggregate, 182-269 parts of fine aggregate, 96-152 parts of modified recycled aggregate powder, 18-24 parts of fly ash, 1.3-2.6 parts of water reducer and 80-100 parts of water.
2. The recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 1, characterized in that: The silicate cement is ordinary silicate cement P.O42.5; the coarse aggregate is stone with a particle size between 4.75-10 mm; the fine aggregate is fine sand with a particle size less than 4.75 mm; and the fly ash is secondary fly ash.
3. The recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 1, characterized in that: The water reducer is one of polycarboxylic acid high-efficiency water reducer CC-AI, polycarboxylic acid high-efficiency water reducer CC-AII and polycarboxylic acid high-efficiency water reducer CC-B.
4. The recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 1, characterized in that: The preparation method of the modified recycled aggregate powder comprises: S1, washing and drying the waste concrete aggregate, and then crushing it in a crusher to obtain waste aggregate powder; S2. Weigh sodium hydroxide powder and deionized water, mix them in a container, stir them thoroughly at room temperature until they are completely dissolved, then slowly pour them into a water glass, stir them thoroughly, and then seal the container and let it stand for 10-16 hours to obtain an activator; S3, then soaking the waste aggregate powder in the activator, stirring continuously for 1-2 hours, filtering and collecting solid particles, and then heating, washing and drying to obtain the preliminary treated waste aggregate powder; S4. Weigh dimethyldimethylaminovinylsilane and add it to anhydrous ethanol, then add the preliminary treated material of waste aggregate powder, soak for 2-4 hours, then add 2-mercaptobenzimidazole, after fully dispersing, irradiate with ultraviolet light and stir for 1-3 hours under the action of initiator, after the treatment is completed, filter and collect the powder, and after drying, the modified recycled aggregate powder is obtained.
5. The recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 4, characterized in that: In S1, the waste concrete aggregate is washed with water for 2-5 times, and dried by air-drying or oven-drying; the crushed concrete aggregate is sieved through a 50-150 mesh sieve.
6. The recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 4, characterized in that: In S2, the modulus of water glass is 1.2-2.8, and the mass ratio of sodium hydroxide powder, deionized water and water glass is 1-3:4-6:10-20.
7. The recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 4, characterized in that: In the S3, the mass ratio of the waste aggregate powder to the activator is 1:2-5; the temperature of the heating treatment is 50-60°C, and the time of the heat preservation treatment is 5-10h; the washing is performed by washing with clean water for 3-5 times; and the drying is performed at 110-120°C for 1-2h.
8. The recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 4, characterized in that: In S4, the mass ratio of the preliminary treated waste aggregate powder, dimethyldimethylaminovinylsilane, 2-mercaptobenzimidazole and anhydrous ethanol is 1:0.1-0.2:0.07-0.15:10-20.
9. The recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 4, characterized in that: In S4, the initiator is photoinitiator 1173 or photoinitiator 907; the wavelength of the ultraviolet light is 365nm, and the light intensity is 10-20mw / cm 2 .
10. A method for preparing the recycled aggregate environmentally friendly crack-resistant ready-mixed concrete according to claim 1, characterized in that: The following steps are involved: Step 1, first mix silicate cement, coarse aggregate, fine aggregate, fly ash and modified recycled aggregate powder into a mortar mixer, and stir at a speed of 50-100 r / min for 2-6 minutes to obtain a first mixture; Step 2, adding a water reducer to water, stirring evenly, and then pouring it into the first mixture, stirring at a speed of 50-100 r / min for 4-10 min to obtain a concrete mixture; Step 3, after the concrete mixture is transported to the use site, it is poured and constructed, and after being vibrated and degassed, it is watered and cured for 7-28 days after being formed, and the environmentally friendly and crack-resistant ready-mixed concrete is obtained.